ANTECEDENTS OF CUSTOMER TRUST AND LOYALTY ON SHOPEE INDONESIA - Dheviolla Andriani Young (Ikatan Dosen Menulis, 2024)
Lack of face-to-face interaction, network and software issues, and inability to touch the product become one of E-commerce constraint. Additionally with the widespread news about unsafe transaction and leak of user’s personal data on e-commerce, lead to decreasing of customer trust toward e-commerce. The decrease of customer trust could impact customer loyalty, if this problem does not resolve. This research is to investigate factors that affect customer trust and loyalty on Shopee among generation Z in context of fashion category, utilizing technology Acceptance Model (TAM). Since Shopee is the top e-commerce with annual growth, while generation Z dominating the e-commerce. Additionally, fashion category is the most category that produce the biggest revenue. Data collected using a survey within 400 respondents that fulfil the requirements. Utilizing descriptive analysis and PLS-SEM, to find whether Perceive Ease of Use (PEoU), Perceive Security (PS), Privacy Concern (PC), Product Variety (PV), and On-Time Delivery (OD) affect Customer Trust (CT), while measuring how Customer Loyalty (CL) affected by Product Variety (PV), On-time Delivery (OD), and Customer Trust (CT). The results indicate that CT relies on PEoU, PS, PC, PV, and OD. While PV, OD, and CT significantly impact CL on Shopee especially generation Z. This research provides e-commerce with insights on which factor influence CT and CL the most. Furthermore, this research aims to contribute to the literature regarding antecedents of trust and customer loyalty in Shopee.